1998
DOI: 10.1681/asn.v93516
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplasia of the juxtaglomerular complex with hyperaldosteronism and hypokalemic alkalosis. A new syndrome. 1962.

Abstract: A new syndrome, characterized by hypertrophy and hyperplasia of the juxtaglomerular apparatus of the kidneys, aldosteronism resulting from adrenal cortical hyperplasia, and persistently normal blood pressure is described in two patients. Overproduction of aldosterone could not be prevented by sodium loading or by administration of albumin intravenously; it was associated with hypokalemic alkalosis and Pitressin-resistant impairment of urinary concentrating ability. In both subjects, increased amounts of circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Moreover, they are positive for PDGFR-β, the common marker of renal interstitial cells and pericytes. Transformation of extraglomerular mesangial cells to renin-producing cells is often observed in situations of chronic salt wasting, for example, due to genetic defects in the aldosterone synthase or in chloride channels, as in Bartter syndrome [ 2 , 30 , 62 , 108 ]. After transformation into renin-producers, EGM cells start to express Akr1b7 [ 54 ].…”
Section: Cells Reversibly Recruited For Renin Productionmentioning
confidence: 99%
“…Moreover, they are positive for PDGFR-β, the common marker of renal interstitial cells and pericytes. Transformation of extraglomerular mesangial cells to renin-producing cells is often observed in situations of chronic salt wasting, for example, due to genetic defects in the aldosterone synthase or in chloride channels, as in Bartter syndrome [ 2 , 30 , 62 , 108 ]. After transformation into renin-producers, EGM cells start to express Akr1b7 [ 54 ].…”
Section: Cells Reversibly Recruited For Renin Productionmentioning
confidence: 99%
“…The syndrome, first described by Bartter et al in 1962 (Bartter et al, 1998), has five different genetic forms (Kleta & Bockenhauer, 2018). Causative genes are directly involved in salt reabsorption in the thick ascending limb of the nephron (BS1‐4) or regulating their expression (BS5).…”
Section: Introductionmentioning
confidence: 99%
“…In the sixties of the last century, Bartter et al [ 1 ] and Gitelman et al [ 2 ] independently observed different cases of patients with electrolyte imbalances, metabolic alkalosis, and salt wasting. These subjects had activation of the renin-angiotensin-aldosterone system (RAAS) and excess of mineralocorticoids yet were normotensive or even had hypotension.…”
Section: Introductionmentioning
confidence: 99%